2023
DOI: 10.3390/s23156811
|View full text |Cite
|
Sign up to set email alerts
|

MSA-YOLO: A Remote Sensing Object Detection Model Based on Multi-Scale Strip Attention

Zihang Su,
Jiong Yu,
Haotian Tan
et al.

Abstract: Remote sensing image object detection holds significant research value in resources and the environment. Nevertheless, complex background information and considerable size differences between objects in remote sensing images make it challenging. This paper proposes an efficient remote sensing image object detection model (MSA-YOLO) to improve detection performance. First, we propose a Multi-Scale Strip Convolution Attention Mechanism (MSCAM), which can reduce the introduction of background noise and fuse multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…It has been proved that convolutional neural networks have satisfied result on crater detection based on DEM and CCD remote sensing data. For example, the FasterRCNN [21] has already been applied in object detection with higher efficiency compared with previous work,MSA-YOLO [22] is desgined to object detection in DIOR dataset, RSI-YOLOv5 [23] is applied in remote sensing dataset such as DOTA and NWPU-VHR with outperform results, and a Graph Neural Network (GNN) [24] is desgined to execute the semantic segmentation in satellite image data. It can be concluded that deep learning method has great potential in remote sensing data processing.…”
Section: Related Workmentioning
confidence: 99%
“…It has been proved that convolutional neural networks have satisfied result on crater detection based on DEM and CCD remote sensing data. For example, the FasterRCNN [21] has already been applied in object detection with higher efficiency compared with previous work,MSA-YOLO [22] is desgined to object detection in DIOR dataset, RSI-YOLOv5 [23] is applied in remote sensing dataset such as DOTA and NWPU-VHR with outperform results, and a Graph Neural Network (GNN) [24] is desgined to execute the semantic segmentation in satellite image data. It can be concluded that deep learning method has great potential in remote sensing data processing.…”
Section: Related Workmentioning
confidence: 99%
“…Considering that precision and recall have an interactive relationship and cannot be directly involved in the evaluation, the concepts of Average Precision (AP) and Mean Average Precision (mAP) are introduced, and the higher the two indicators are, the better the detection is; see Equations ( 26) and (27).…”
Section: Evaluation Indicatorsmentioning
confidence: 99%
“…For remote sensing monitoring, Li et al [ 26 ] improved the detection precision of small-resolution images by incorporating an attention mechanism into YOLOv5, a bidirectional feature pyramid, and a small-targets detection layer. In contrast, Su et al [ 27 ] lightened the YOLOv5 module and optimized the loss function to enhance the network’s detection performance for remote sensing images.…”
Section: Introductionmentioning
confidence: 99%